Communicative activities in teaching grammar at Tran Phu High School, Thai Nguyen - Mai, Thi Thai (University of Languages and International Studies, 2017)
The study explores communicative activities in teaching grammar at Tran Phu School, Thai Nguyen. The study seeks to find out the methods that have been used to teach English grammar at Tran Phu School; the extent that the application of communicative activ (...)